An evaluation of an innovative screening program based on risk criteria for early diagnosis of head and neck cancers - Zabala, Aitor; Martín-Arregui, Francisco Javier; Sagazola, Jon; Santaolalla, Francisco Javier; Santaolalla, Francisco (Frontiers in Public Health, 2023)
Introduction Head and neck cancer represents 3% of all cancers and is the cause of 5% of the deaths caused by cancer. The purpose of this study is to evaluate the implementation of a screening program to diagnose the early phase of the head and neck oncological processes. Methods We have studied 324 asymptomatic patients who had at least one major risk factor (habitual consumption of tobacco or alcohol) or two minor risk factors: family history of head and neck cancer of the upper aerodigestive tract, occupational exposure, poor oral hygiene and history of Human Papillomavirus or chronic inflammatory processes of the aerodigestive tract. Family and personal head and neck oncological medical history, ENT exploration, performance of CT scans or biopsies and program procedures were analyzed. Results The most usual referral criteria for being sent to a specialist was being a smoker (98.1%). 10.5% reported family histories of head and neck cancer, 9.9% reported occupational exposure, 7.1% were referred due to poor oral hygiene and 5.9% were referred for gastroesophageal reflux disease. Although being asymptomatic was a requirement for inclusion, we verified that, after the anamnesis, 9.6% of the patients had some symptom to which they did not give importance to 119 patients (36.7%) presented a lesion that potentially could become malignant, located in the larynx and hypopharynx (25%) and in the oral cavity and oropharynx (10.8%). Eighteen patients (5.56%) presented more than one lesion. The detection rate of neoplasia was 1.2% and the detection rate of pre-neoplastic lesions was 4.6%. There did exist a statistically significant ratio between the detection of pre-neoplastic lesions and occupational exposure to carcinogenic agents (p = 0.006), poor oral hygiene (p = 0.01) and gastroesophageal reflux disease (p = 0.007). Samples were taken for a pathological anatomy study in 30 patients (9.25%). In order to follow up the patients, 22.8% were controlled at hospital medical consultations, 11.1% were examined at outpatient consultation and 66% were given appointments for follow-up visits. Conclusions The use of this screening program could be a tool for the early diagnosis of malignant head and neck tumors and to foster healthy habits for cancer prevention.